Field reports form for submitting seasonal observations of Iowa birds, Jan L. Walter, fall 1988 - Walter, Jan L.et al (1988)
List of birds and locations contributed by Jan L. Walter with observers Jim B. Walter and Curt Nelson. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of fall 1988. Epson - sheet feed